2021
DOI: 10.1042/bcj20210077
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotubes and related structures: molecular mechanisms of formation and function

Abstract: Tunneling nanotubes (TNTs) are F-actin-based, membrane-enclosed tubular connections between animal cells that transport a variety of cellular cargo. Over the last 15 years since their discovery, TNTs have come to be recognized as key players in normal cell communication and organism development, and are also exploited for the spread of various microbial pathogens and major diseases like cancer and neurodegenerative disorders. TNTs have also been proposed as modalities for disseminating therapeutic drugs betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 185 publications
0
27
0
Order By: Relevance
“…(a) Tunneling nanotubes (TNTs) are a new form of direct contact interaction among cells, as they help cells to "talk" directly with each other over lengthier spaces [4][5][6] (Figure 1a). This breakthrough contested the classical view of cells, the basic unit of organisms, as separate elements.…”
Section: Introduction 1general Considerations On Tunneling Nanotubesmentioning
confidence: 99%
“…(a) Tunneling nanotubes (TNTs) are a new form of direct contact interaction among cells, as they help cells to "talk" directly with each other over lengthier spaces [4][5][6] (Figure 1a). This breakthrough contested the classical view of cells, the basic unit of organisms, as separate elements.…”
Section: Introduction 1general Considerations On Tunneling Nanotubesmentioning
confidence: 99%
“…Here, they visualized quantum dots (QD) of CdSe/ZnS being transported along "newly discovered nanotubular structures" formed between rat cardiac myoblast cells. In fact, this study pioneered the idea that NMeds could be transported via TNTs inside membrane vesicles, and that the exchange could be bidirectional, which would afterwards be confirmed by successive publications [131,132]. Similarly, in the following year, Mi et al, reported the intercellular transfer of CdTe QD along TNTs in human hepatocellular carcinoma cells [133].…”
Section: Inorganic Nmedsmentioning
confidence: 61%
“…Generally, TNTs are accepted to be thin tubes interconnecting two cells with both open-ended connections. As a result, TNTs can transport materials between cells, including small molecules; macromolecules, such as proteins; and even organelles, such as mitochondria 47,48 . The mechanisms underlying the formation of TNTs are unclear.…”
Section: Deregulated Phosphorylation By Overexpression and Hyperactiv...mentioning
confidence: 99%
“…Some have proposed that they originate from lamellipodium-or filopodium-like membrane protrusions, which are specialized membrane structures at the leading edge of the cells 49,50,51 . Once a membrane protrusion reaches another cell, a fusion process driven by an unknown mechanism can occur, leading to an interconnected TNT 48,52 . Our characterization of tubular structures decorated by the EphB6:ephrinB1 coclusters indicates that they are distinct from TNTs, because the co-clusters rely on the interaction of EphB6 and ephrinB1 in trans.…”
Section: Deregulated Phosphorylation By Overexpression and Hyperactiv...mentioning
confidence: 99%